Inflation Targeting and Communication : It Pays Off to Read Inflation Reports - Smidkova, Katerina; Bulir, Ales.; Kotlan, Viktor; Navratil, David (Washington, D.C. : International Monetary Fund, 2008)
Inflation-targeting central banks have a respectable track record at explaining their policy actions and corresponding inflation outturns. Using a simple forward-looking policy rule and an assessment of inflation reports, we provide a new methodology for the empirical evaluation of consistency in central bank communication. We find that the three communication tools-inflation targets, inflation forecasts, and verbal assessments of inflation factors contained in quarterly inflation reports-provided a consistent message in five out of six observations in our 2000-05 sample of Chile, the Czech Republic, Hungary, Poland, Thailand, and Sweden.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet